2010
DOI: 10.1128/ec.00259-09
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Evolutionary Trajectory of the Mating Type (MAT) Locus in Dermatophyte and Dimorphic Fungal Pathogens

Abstract: Sexual reproduction in fungi is governed by a specialized genomic region, the mating type (MAT) locus, whose gene identity, organization, and complexity are diverse. We identified the MAT locus of five dermatophyte fungal pathogens (Microsporum gypseum, Microsporum canis, Trichophyton equinum, Trichophyton rubrum, and Trichophyton tonsurans) and a dimorphic fungus, Paracoccidioides brasiliensis, and performed phylogenetic analyses. The identified MAT locus idiomorphs of M. gypseum control cell type identity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 64 publications
2
82
0
Order By: Relevance
“…Of these, the α-box protein encoding gene, MAT1-1-1 (Coppin et al 1997;Debuchy and Turgeon 2006), was first identified in Saccharomyces cerevisiae (Astell et al 1981) and has subsequently been identified in all fungal MAT1-1 idiomorphs ; Kanematsu et al 2007;Li et al 2010). The MAT1-1-2 gene encodes an amphipathic α-helix protein with a conserved Histidine, Proline, Glycine (HPG) domain (Debuchy and Turgeon 2006), while the MAT1-1-3 gene encodes a protein with a High Mobility Group (HMG) domain (Coppin et al 1997;Debuchy and Turgeon 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the α-box protein encoding gene, MAT1-1-1 (Coppin et al 1997;Debuchy and Turgeon 2006), was first identified in Saccharomyces cerevisiae (Astell et al 1981) and has subsequently been identified in all fungal MAT1-1 idiomorphs ; Kanematsu et al 2007;Li et al 2010). The MAT1-1-2 gene encodes an amphipathic α-helix protein with a conserved Histidine, Proline, Glycine (HPG) domain (Debuchy and Turgeon 2006), while the MAT1-1-3 gene encodes a protein with a High Mobility Group (HMG) domain (Coppin et al 1997;Debuchy and Turgeon 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, comparisons of MAT DNA sequences in different fungi have improved our understanding of the evolution of homothallic and heterothallic mating strategies (Arie et al 1997;Bennett et al 2003;Conde-Ferráez et al 2007;Fraser and Heitman 2004;Li et al 2010;Martin et al 2011;Steenkamp et al 2000;Turgeon 1998). Also, the availability of information on the mating idiomorphs allowed for the assessment of the presence of MAT genes in the genome of apparently asexual species (Foster and Fitt 2003;Mandel et al 2007;Turgeon 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since the MAT locus genes are intact and major meiotic genes are conserved in the completed genomic sequences from four different H. capsulatum isolates, this loss of mating ability could involve epigenetic factors. In Microsporum gypseum, cleistothecium formation and the production of asci and ascospores were observed by mating assays (160,302). By scanning electron microscopy, the cleistothecium was found to be enveloped by coiled and spiral hyphae.…”
mentioning
confidence: 97%
“…Our study indicates that transitions to unisexual reproduction from bisexual reproduction may not inevitably lead to Muller's ratchet and an evolutionary dead end, as previously hypothesized (Bell 1982;Charlesworth et al 1993;Lynch et al 1995;Paland and Lynch 2006;Gioti et al 2013). In addition, many pathogenic eukaryotes are thought to have clonal population structures, but recent work has uncovered evidence of cryptic sexual or unisexual cycles (Gräser et al 1996;Peever et al 1999;Berbee et al 2003;Heitman 2006;Morgan et al 2007;Heitman 2010;Li et al 2010;Farrer et al 2011;Stewart et al 2013;Roach et al 2014). Human pathogens of significant public health concern, such as those from the Leishmania, Trypanosoma, and Toxoplasma genera, show signatures of recombination and unisexual cycles (Jenni et al 1986;Gaunt et al 2003;Akopyants et al 2009;Wendte et al 2010;Minot et al 2012).…”
Section: Discussionmentioning
confidence: 99%